Urbanorum: a case of scientific negligence - Carlos Ramiro Silva-Ramos (Asociación Colombiana de Infectología, 2024)
A recent report described one diarrheic episode that clinically responded to metronidazole as due to "Urbanorum spp" in Ecuador1. In this Ecuadorian case report differential diagnosis was mentioned only as done by the results from a reference laboratory, but without details of immunological or special stool stains, such Kinyoun, to discard other etiologies. The authors wrote that diagnosis was based on microscopic observation of structures like those reported in 1994, by Professor Francisco Tirado Santamaría from the Universidad Industrial of Santander, but when you look for the reference of this "scientific work" you found a webpage destinated to store undergraduate student ́s homework documents1. The lack of description of confirmatory tests in cases published in one journal ranked Q3 in Scopus (American Journal of Case Reports) highlights the necessity of scientific evaluation with high standards for case reports. Infectio have a refusal rate of 70% for clinical case reports, mostly justified because these are not accompanied by a microbiological confirmation of the species. The original description of Professor Tirado is not available in scientific journals and does not comply with the minimum rules that need to be considered as a new parasite organism2.